Parameter identification of the photovoltaic panel’s two-diode model - Madi, Saida; Saoudi, Kamel (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This work deals with the two-diode model of a photovoltaic (PV) panel. It provides the per-unit energy and current representations in addition to identifying its unknown parameters. Mathematical equations have been proposed and built using the MATLAB/Simulink simulator to achieve this goal. Only one variable has been adjusted to get all the unknown parameters simultaneously at standard test conditions (STC). Three variables have to be adjusted under any other atmospheric conditions. Two different technologies have been used. The accuracy of the proposed mathematical model has been provided using the absolute relative error between the simulated value and the measured one. The biggest values of the absolute relative error are 0.000788%, 0.0006157%, and 0.000616% under STC, nominal cell temperature condition (NOCT), and random daily atmospheric conditions, respectively.